Microbiological analysis of surfaces in butchers of the municipal market of Cuiabá/ Análisis microbiológico de superficies en carnicerías del mercado municipal de Cuiabá/ Análise microbiológica de superfícies em açougues do mercado municipal de Cuiabá - Lara, Evangreize; Felix, Camila Laturner; Duarte, Tiffany Dias; Vivi, Viviane Karolina (Journal Health NPEPS, 2019)
Objective: to isolate enterobacteria, especially the thermotolerant, present on the surfaces of knives, trays and cutting boards used in the handling of meat in butchers. Method: cross-sectional study, conducted from April to October 2017 in nine establishments that sell meat products in Cuiabá – Mato Grosso, Brasil. Surface samples were collected from three different utensils: knife, board and tray. Results: Among utensils used on handling poultry meat, the knife got greater growth of enterobacteria (4,36x104 UFC/cm2). The cutting board intended for pork also reported higher 7,44x104 UFC/cm2. For beef, the tray and the board respectively, had scores of 2,5x105 UFC/cm2 and 2,41x105 UFC/cm2. The high growth of enterobacteria is justified by the grooves contained in these tools, poor maintenance and hygiene. It was also observed the presence of 27% of fecal coliforms and 73% of total coliforms. Conclusion: from the data obtained it is inferred that the hygienic and sanitary conditions are not in accordance with the RDC No. 216/2004.